Complete mitochondrial genome of Schizothorax davidi (Teleostei: Cypriniformes: Cyprinidae) - Shuo Feng; Zhifang An; Yue Wang; Jian Liang (Mitochondrial DNA. Part B. Resources, 2019)
This study provides a mitochondrial complete genome of Schizothorax davidi. The complete genome is 16,576 bp in length with an A + T content of 54.9%, which contains 13 protein-coding genes, 22 tRNA genes, and 2 rRNA genes. The phylogenetic analysis indicated that S. davidi is closely related to Schizothorax lissolabiatus. These results contribute to explore the adaptation strategy of S. davidi on the conditions of Qinghai-Tibet Plateau.